Tax Management of Manufacturing Company Listed on The Indonesia Stock Exchange (IDX) - Atik Djajanti; Tia Andriani (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze tax management of manufacturing companies listed on the Indonesia Stock Exchange. Determinants of tax management under this study consist of financial performance and good corporate governance (GCG). The highlighted financial performance consists of profitability, leverage, company size, and inventory intensity. The population consisted of manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange for the period 2015–2019. The sample was selected by a purposive sampling method. Data analysis used multiple linear regression with the help of the SPSS version 25 statistical application. Before testing the hypothesis, the data was confirmed that it had passed the classical assumption test. The results show that profitability affects tax management. This proves that Compay with higher profitability paid the lower Effective Tax rate (ETR). Other financial performance variables such as leverage and inventory intensity do not affect tax management. The firm size variable proves that larger company size, higher the ETR. GCG, which is proxied as a percentage of independent commissioners, shows that it can affect tax management.